2013 American Control Conference 2013
DOI: 10.1109/acc.2013.6580444
|View full text |Cite
|
Sign up to set email alerts
|

Direct control implementation of a refrigeration system in smart grid

Abstract: Abstract-The thermal capacity of the content in a cold storage room renders it possible to shift the governing refrigeration system's power consumption in time, without compromising temperature constraints. In this paper we introduce a method of implementing such a cold storage room into a directly controlled smart grid, by use of a predictive control strategy. In this application the shift in consumption is used to stabilize a small grid by utilizing excess renewable energy to minimize the need for fossil fue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…When modelling the evaporator, we assume that the temperature of the refrigerated goods is the same as the temperature in the display case (Larsen (2005) and Pedersen et al (2013)); hence, we do not take the heat transfer between evaporator-air and air-food into consideration. Furthermore, we disregard the dynamics of the expansion valve, and model the evaporator assuming that cooling capacity can be controlled as in Shafiei et al (2013).…”
Section: Assumptionsmentioning
confidence: 99%
See 1 more Smart Citation
“…When modelling the evaporator, we assume that the temperature of the refrigerated goods is the same as the temperature in the display case (Larsen (2005) and Pedersen et al (2013)); hence, we do not take the heat transfer between evaporator-air and air-food into consideration. Furthermore, we disregard the dynamics of the expansion valve, and model the evaporator assuming that cooling capacity can be controlled as in Shafiei et al (2013).…”
Section: Assumptionsmentioning
confidence: 99%
“…In Shafiei et al (2013), Hovgaard et al (2011), Hovgaard et al (2012), authors present various forms of linear economic MPC for supervisory control. In Pedersen et al (2014), Pedersen et al (2013), the authors use a "leaky bucket" model for high level representation of groups of refrigeration units and solve the optimization problem using linear economic MPC as well. Nonlinear MPC for vapour compression cycle system has been demonstrated in Leducq et al (2006).…”
Section: L(x(t) U(t))dtmentioning
confidence: 99%
“…Since, this topic has received much attention research perspective [11], [12], [13]. A few research examples in the area of smart grid DER control are: optimization of domestic heat pumps [14], [15], supermarket cooling systems [16], [17], domestic refrigerators [18], [19], and electrical vehicles [20], [21]. While these works, and many more, discuss methods for remote control of DERs, they do not discuss who the DERs should communicate their flexibility to the VPP.…”
Section: Introductionmentioning
confidence: 99%
“…Hovgaard et al [2012] presents an MPC algorithm to optimize cost of operation as well as providing normal ancillary services, where a non-convex optimization problem is put forward. Direct control implementation of single vapor compression cycle (VCC) is presented in Pedersen et al [2013] where a simple bucket model is introduced for energy modeling of the system. It is shown that how the flexible power consumption of refrigeration systems can be employed for minimization of the fossil fuel production sources in a small grid.…”
Section: Introductionmentioning
confidence: 99%